Health in hard times : austerity and health inequalities - Bambra, C. (Clare) (Policy Press, 2019)
Health in hard times is a vital and important review of the impact of austerity on the wellbeing of the UK. Case studies from Stockton-on-Tees, home to some of the starkest health divides, are combined with a holistic review of the repercussions of budget cuts and welfare reforms to provide a portrait of inequalities in the country's health today.